COMPARISION OF LICHTESTEIN OPEN TENSION-FREE VERSUS LAPROSCOPIC TOTALLY EXTRAPERTIONEAL TECHNIQUE FOR INGUINAL HERNIA REPAIR - SHARMA, VINEET; BHARDWAJ, GIRISH; SAINI, VIVEK; PORWAL, PANKAJ; TRIPATHI, ANIL KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The study aimed to assess and compare Litchtenstein’s open tension-free and laparoscopic totally extraperitoneal (TEP) mesh repair. Methods: This hospital-based comparative type of observational study was conducted on 50 cases for each of two groups at upgraded Department of General Surgery, SMS Hospital, Jaipur, between January 2014 and January 2016. All the cases of elective inguinal hernia coming to SMS outpatient department in a single surgical unit operated by a single surgeon in the given period which meet the inclusion and exclusion criteria. Thus, collected data were entered in Microsoft Excel sheet and analysis was done by Epi info software of CDC. Results: Total 100 patients were included in this study; 50 each in the two groups, the laparoscopic TEP group and open Lichtenstein group. Mean age in the laparoscopic group was 39.54 years and the open Lichtenstein group was 42.78 years. The mean pain score out of 10 at 24 h was 2.96 (±0.638) and 3.60 (±0.969) in TEP and Lichtenstein groups, respectively. The mean return to work for open group was 17.00 and TEP group was 11.34 days. There is no any recurrence and readmission in both groups. Conclusion: Laparoscopic TEP repair may be done in all uncomplicated inguinal hernia by an experienced surgeon for those desiring less pain, better cosmotic results, less post-operative complications, less hospital stay, and early return to work.